The Perils of Privatization: Bringing the Business Model into Human Services. Issue 3 (14th August 2020) - Zelnick, Jennifer R; Abramovitz, Mimi
Abstract: During the last three decades in both the United States and Europe, neoliberal policies, especially privatization, have restructured services in ways that dramatically affect the capacity of human services workers and agencies to serve all clients. Privatization means not only transforming public programs such as Social Security, but also managerialism —the incorporation of business principles, methods, and goals into public and nonprofit human services organizations. Few researchers have looked at the impact of market-based managerialism (focused on productivity, accountability, efficiency, and standardization) on social work's mission and the effectiveness of human services workers and organizations. Using an anonymous survey of 3, 000 New York City human services workers, authors examined the impact of managerialist practices including performance measures, quantifiable short-term outcomes, and routinized practices on frontline workers and service provision. A troubling trend emerged. Workers in agencies with a high commitment to managerialism found it considerably more difficult to adhere to social work's mission and fundamental values. This conflict between the "logic of the market" and the "logic of social work" subsided dramatically in agencies with a low commitment to managerialism, indicating that even in today's competitive environment, agencies can protect the social work mission.